The Role of Socioeconomic and Cultural Factors in Shaping Healthcare Accessibility - Setiadi (Moneta : Journal of Economics and Finance, 2024)
Access to healthcare remains a critical concern globally, particularly in low- and middle-income countries where systemic barriers persist. This narrative review aims to examine the multi-layered factors influencing healthcare access, including social, economic, policy, and cultural dimensions. Literature was sourced from major scientific databases such as PubMed, Scopus, and Web of Science using key terms like "healthcare access," "health equity," and "public health policy." The selection criteria emphasized peer-reviewed studies focusing on determinants of access to health services across various geographical contexts. Findings demonstrate that educational level, social stratification, and income disparities significantly shape individuals' ability to seek and receive healthcare. Cultural beliefs and stigmas further limit service utilization, especially for chronic and stigmatized conditions. Moreover, policies that are not evidence-based or fail to account for local realities often exacerbate existing inequities. Although countries like Sweden have implemented successful universal health programs, their replication requires context-sensitive adaptation. The discussion reveals that bureaucratic inefficiencies and systemic inequalities perpetuate inaccessibility, highlighting the need for more responsive and community-centered health policies. In conclusion, this study calls for integrative approaches that combine education, policy reform, and culturally aligned interventions to bridge healthcare gaps. It recommends future research on localized service models and the expansion of digital health education tools to enhance access and equity.